2020
DOI: 10.1007/s12325-020-01250-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective β-Blockers May Progress the Thrombosis of Portal Venous System in Cirrhotic Patients: A Retrospective Observational Study

Abstract: Introduction: Occlusive portal venous system thrombosis (PVT) is significantly associated with poor outcomes in cirrhotic patients. Nonselective b-blockers (NSBBs) may be associated with the development of PVT. However, the role of NSBBs in progressing thrombosis remains unclear. Methods: Forty-three patients on whom contrast-enhanced computed tomography or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Compensated cirrhosis is associated with a higher portal vein recanalization rate; by comparison, patients with Child-Pugh class B and C and higher MELD score have a lower portal vein recanalization rate. Advanced liver cirrhosis has an aggravation of portal hypertension and a higher probability of using non-selective beta-blockers, thereby reducing the portal vein blood flow velocity which may contribute to the development and progression of PVT [ 55 , 56 ]. In addition, patients with advanced cirrhosis are more prone to the risk of thrombotic events and resistance to anticoagulation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compensated cirrhosis is associated with a higher portal vein recanalization rate; by comparison, patients with Child-Pugh class B and C and higher MELD score have a lower portal vein recanalization rate. Advanced liver cirrhosis has an aggravation of portal hypertension and a higher probability of using non-selective beta-blockers, thereby reducing the portal vein blood flow velocity which may contribute to the development and progression of PVT [ 55 , 56 ]. In addition, patients with advanced cirrhosis are more prone to the risk of thrombotic events and resistance to anticoagulation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 A retrospective study also proved that NSBB was significantly associated with PVT progression (OR = 4.400, 95% CI: 1.107–17.482, p = 0.035). 33 Besides, a meta-analysis demonstrated that use of NSBB progressed PVT (OR = 4.62, 95% CI: 2.50–8.53, p < 0.00001) and subgroup meta-analyses also manifested a consistent association between NSBB and PVT in both cohort studies (RR = 2.57, 95% CI: 1.46–4.51, p = 0.001) and case–control studies (OR = 8.17, 95% CI: 2.46–27.06, p = 0.0006). 34 Therefore, increased risk of PVT development brought by NSBB application might put management of variceal bleeding complicated with PVT into jeopardy.…”
Section: Discussionmentioning
confidence: 99%
“…Although NSBBs play an important role in the prevention of variceal rebleeding, there are still a series of problems, such as NSBB-related side effects and the use of NSBBs in cirrhotic patients with spontaneous bacterial peritonitis, and refractory ascites is still controversial [ 25 ]. In addition, studies have shown that the use of NSBBs is a risk factor for portal vein thrombosis [ 26 28 ]. In our study, two patients who took propranolol decreased from 80 mg/d to 60 mg/d due to decreased heart rate, and no obvious adverse reactions were found in other patients.…”
Section: Discussionmentioning
confidence: 99%